Sistem Informasi Perpustakaan pada SMK Wiyata Satya (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
This study aims to analyze and improve the library information system at SMK Wiyata Satya. The background of this study focuses on the importance of efficient data management in the process of borrowing and returning books. The method used in this study is a qualitative descriptive approach by conducting literature studies, observations, interviews, and distributing questionnaires to students and library staff. The results of the questionnaire indicate that there is an urgent need for a computerized system to facilitate data collection and storage of information. From the data analysis, it was found that 35.4% of respondents agreed with the need for a new system, while 27.1% strongly agreed. These results indicate that the majority of respondents are aware of the importance of a better information system to improve the efficiency of library operations. The conclusion of this study emphasizes that the implementation of a computerized information system at SMK Wiyata Satya will not only improve efficiency, but will also provide convenience in managing library data. Thus, it is hoped that this study can be a reference for the development of library information systems in other educational institutions. This study is expected to provide a positive contribution in improving the quality of library services at SMK Wiyata Satya.